(untitled) (Biological Sciences - PJSIR, 1996)
Some pyridine substituted heterocyclic compounds and their derivatives such as, imidazolone, quinazolone, ben- zimidazole, phthalimide, thioxopyrimidindione, pyrazole, l,2,4-triazinone and thiazolidinone (IYcXXYII) have been prepared and screened for their antibacterial and antifungal activities, which gave encouraging results: The structures of the products have been verified by elemental analysis and spectral data (IR, UY, IH NMR and mass).